Individually controlled noise reducing devices to improve IEQ in classrooms of primary schools - Dadi Zhang (A+BE: Architecture and the Built Environment)
In recent decades, many indoor environmental quality (IEQ) related problems (such as noise, odour, overheating, glare…) in classrooms have been identified. The impact of IEQ in classrooms on school children has been thoroughly researched. Consequently, many studies have been carried out to attempt to improve the IEQ in classrooms. However, most of the IEQ-improvements were developed based on general requirements and ignored individual differences. No matter how advanced these improvements are, always some children keep being unsatisfied with the IEQ in their classrooms. Given the fact that different children have different IEQ perceptions, preferences, and needs, it makes more sense to control the IEQ in classrooms on the level of the individual rather than of the room. Only by doing this can the comfort, health, and ultimately performance of school children be improved. For this reason, this research explored the possibility of customizing IEQ in classrooms of primary schools in the Netherlands. This thesis addressed the following topics: